Adaptive Control of Multivariable Systems with Reduced Knowledge of High Frequency Gain: Application of Dynamic Regressor Extension and Mixing Estimators⁎. Issue 15 (2018) - Gerasimov, D.; Ortega, R.; Nikiforov, V.
Abstract: In this paper we provide a new solution to the problem of adaptive stabilization of linear multivariable systems of relative degree one with reduced prior knowledge of the high frequency gain—imposing only a full-rank condition to this matrix. Instrumental for the establishment of our result is the use of the parameter estimation technique of dynamic regressor extension and mixing recently proposed in the literature. This estimator is used to update the parameters of the classical output-feedback controller, hence the controller is smooth and does not require any projections nor overparameterizations.